2019
DOI: 10.1186/s12879-019-4189-7
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide study of multidrug-resistant tuberculosis in Portugal 2014–2017 using epidemiological and molecular clustering analyses

Abstract: Background Increasing multidrug-resistant tuberculosis (MDR-TB) incidence is a major threat against TB eradication worldwide. We aim to conduct a detailed MDR-TB study in Portugal, an European country with endemic TB, combining genetic analysis and epidemiological data, in order to assess the efficiency of public health containment of MRD-TB in the country. Methods We used published MIRU-VNTR data, that we reanalysed using a phylogenetic analysis to better describe MDR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This high clustering rate reflects the underlying endemicity of the described clades in Portugal but, upon closer inspection of genomic clusters, the heterogenic composition of these clusters regarding drug resistance type and profiles also suggests the de novo emergence of MDR-TB in such clusters. Recent data obtained from MIRU-VNTR typing supports an epidemiological setting marked by uncontrolled MDR-TB transmission 47 . The situation is not novel, and the mostly represented MIRU-VNTR clusters therein identified have been previously described 5,48 .…”
Section: Discussionmentioning
confidence: 86%
“…This high clustering rate reflects the underlying endemicity of the described clades in Portugal but, upon closer inspection of genomic clusters, the heterogenic composition of these clusters regarding drug resistance type and profiles also suggests the de novo emergence of MDR-TB in such clusters. Recent data obtained from MIRU-VNTR typing supports an epidemiological setting marked by uncontrolled MDR-TB transmission 47 . The situation is not novel, and the mostly represented MIRU-VNTR clusters therein identified have been previously described 5,48 .…”
Section: Discussionmentioning
confidence: 86%
“…Regarding hotspots of MDR-TB, 7 out of the 8 high-risk areas are located in the Lisbon metropolitan area. Previously identified MDR-TB genetic clusters revealed evidence of transmission of multidrug-resistant strains in this region 31 33 .…”
Section: Discussionmentioning
confidence: 93%
“…As previously described, 61% of the incidence of MDR-TB among previously treated patients resulted from MDR-TB transmissio 5 . In fact, genetic studies 31 33 suggested that a high percentage of these cases in Portugal were related with the transmission of two stable MDR-TB clusters.…”
Section: Discussionmentioning
confidence: 99%
“…All patients, however, reported that family members and other contacts had been called to the CDP for disease and infection screening. Recent studies conducted in Portugal, combining a strain genotyping analysis with epidemiological data from MDR-TB cases, have confirmed strong epidemiological links [19].…”
Section: Discussionmentioning
confidence: 99%